Утицај пројекта Европске престонице културе на имиџ града Новог Сада - перцепција локалне заједнице - Kovačić, Sanja; Vujičić, Miroslav; Čikić, Jovana; Šagovnović, ivana; Stankov, Uglješa; Zelenović Vasiljević, Tamara (Turizam, 2020)
Nowadays, the research focus is mainly on how tourists perceive the destination image, while the local community, as a very important key actor, is very often neglected in the studies. In light of the fact that Novi Sad has been declared the European Capital of Culture 2021, great attention has been placed on the local community and its perception of the European Capital of Culture (ECoC) influence on all aspects of the city’s life, including city image. In this regard, during April and May 2018, a survey of residents of Novi Sad was conducted to explore their perception of the city’s image - cognitive, affective, and overall. In this study, which is the beginning of a longitudinal study aiming to follow the influence of the ECoC project on the city image, a total of 797 respondents participated. The results of the research on the cognitive image indicate that the local community mostly agrees with the claims that Novi Sad is a pleasant place to live in, that it has a good gastronomic offer, is an attractive place for education, and that people are kind and hospitable. On the other hand, the smallest degree of agreement is observed with claims which refer to the living standard in the city. When it comes to tourism and culture, significant differences are observed between individual attributes. Also, research on the affective image shows that the city is perceived as relaxing, pleasant, exciting, and lively.